Delegation practices of three selected high school principals - Tarroza, Leticia M. (Animo Repository, 1978)
This project paper sought to design a functional model of delegation of an autonomous high school with a negative income and whose enrollment is between 300 to 500. The model delegation sought to identify and determine what tasks of the principal, categorized broadly as functions of planning, decision-making, reporting and supervision, can and cannot be delegated. Specifically, it sought to answer the following questions : What tasks of the principal may be delegated? To whom may some of the tasks of the principal be delegated? The study limits its subject area of survey to three principals assigned in three rural secondary schools all located in the municipality of Dumanjug, Cebu. The respondents concerned were the principal of Little Flower School, Bitoon Barangay High School, and Cogon Barangay High School, all located in the same municipality. The method used in the study was a descriptive survey method. The writer made use of the pre-tested survey questionnaire prepared by the Educational Management Center of De La Salle University, Manila. The survey specifically concerned with drawing out from the principals of said schools, information on the delegated and non-delegated practices of managerial functions in areas of planning, decision-making, reporting, and supervision. After careful examination of the questionnaire, options were made to draw an organizational model of delegation. Model of delegation typical of a Type II School was the one chosen to be developed.